Volkswagen : engineering a disaster - Bourg-Meyer, Vero, (SAGE Business Cases., 2018)
In 2015, the United States Environmental Protection Agency (EPA) discovered that German automaker Volkswagen A.G. (VW) used software to cheat air emissions testing in about 590,000 "clean diesel" vehicles under the Volkswagen, Audi, and Porsche nameplates in the United States. All told, VW included the software defeat switch in about 11 million diesel cars worldwide. Some assessed that up to 1,000 employees in the organization had known about the fraud and kept silent for over a decade.